Short Communication: Identification of Growth Hormone gene polymorphism for beef cattle in Pesisir Selatan District, West Sumatra, Indonesia - DINO EKA PUTRA; SUMADI SUMADI; TAKUYA KANAZAWA; TETY HARTATIK (Society for Indonesian Biodiversity, 2016)
Putra DE, Sumadi, Kanazawa T, Hartatik T. 2016. Short Communication: Identification of Growth Hormone genepolymorphism for beef cattle in Pesisir Selatan District, West Sumatra, Indonesia. Biodiversitas 17: 711-715. This study aimed to determine gene polymorphism of growth hormone of domestic cattle in Pesisir Selatan District of West Sumatra. The research was conducted at Laboratory of Animal Genetics and Breeding Faculty of Animal Science, UGM from August 2013 to January 2014. Blood samples were collected from 66 individuals consist of 15 Pesisir cattle, 15 SimPes cattle, 15 SimPO cattle, 15 Bali cattle and 6 PO cattle. DNA was extracted from each blood samples after SDS-proteinase K digestion, and used for PCR-amplification for a region of growth hormone gene (211 bp), and then the PCR products were analyzed for restriction fragment length polymorphism (RFLP) using AluI restriction enzyme. The results showed that GH gene of Pesisir, PO and Bali cattle are monomorphic, which frequencies of L allele was1.00 and V allele was 0.000 while these LL genotype was 1.000. Frequency of L and V alleles in SimPO and SimPes cattle were 0.634, 0.366 and 0.700, 0.300, respectively. SimPO and SimPes cattle were polymorphic, LL and LV of SimPO cattle was 0.733 and 0.267 as well as SimPes cattle which LL and LV was 0.600 and 0.400, respectively. The correlation between genotype and the performance (body weight and body size) was not significant. The present study indicates that polymorphism of growth hormone gene in AluI site could not yet be used as a molecular marker for body weight and body size of beef cattle.